Effects Of Business Upgrading Programs On Their Competitiveness: Systematic Review And Meta-Analysis - Theodory, Yana; Mbue Innocent, Ndoh (Publisher Cv. Inara, 2022)
The advent of free trade subjects' businesses in underdeveloped countries and economies in transition to the challenges of competitiveness and competition. To overcome these constraints, upgrading programs have been adopted as public policy. This review aims to identify the impacts of programs on their competitiveness and analyze the relationship between the variables of said programs and their effects. Sixty-three studies (63) are identified from online databases with arithmetic means as follows: Hindawi, n = 36, 0.22%; Google Scholar, n=33, 0.20%; Scorpus, n=33, 0.20%; and Google search, n = 31, 0.19% with specific Search terms such as